2013
DOI: 10.4103/0976-237x.114878
|View full text |Cite
|
Sign up to set email alerts
|

Resistin in serum and gingival crevicular fluid as a marker of periodontal inflammation and its correlation with single-nucleotide polymorphism in human resistin gene at −420

Abstract: Aims:Resistin is an adipocytokine, which have been studied for its role in insulin resistance and recently in inflammation. The aim of the present study is to assess the concentration of resistin in serum and gingival crevicular fluid (GCF) and to compare the levels between subjects with and without periodontitis and type 2 diabetes mellitus (T2DM) and to further correlate the resistin levels with the single-nucleotide polymorphism (SNP) at −420.Setting and Designs:A total of 96 subjects (48 males and 48 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…Increased serum levels of RETN were found with periodontal inflammation, which indicates a potential inflammatory role in periodontitis. 8 Increased RETN serum levels were also significantly associated with periodontal condition and there was also a trend towards decreased levels of ADIPOQ in subjects with periodontitis in a Japanese population. 34 Saito et al 35 concluded that increased RETN serum levels in middle-aged Japanese women with periodontitis may affect their systemic health.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Increased serum levels of RETN were found with periodontal inflammation, which indicates a potential inflammatory role in periodontitis. 8 Increased RETN serum levels were also significantly associated with periodontal condition and there was also a trend towards decreased levels of ADIPOQ in subjects with periodontitis in a Japanese population. 34 Saito et al 35 concluded that increased RETN serum levels in middle-aged Japanese women with periodontitis may affect their systemic health.…”
Section: Discussionmentioning
confidence: 91%
“…Candidate genes that encode adipokines and their specific genetic variants were selected based on previously described associations in other populations, 7,8 their possible functional impacts on the etiopathogenesis of CP, a minor allele frequency (MAF) higher than 0.1 in the European Caucasian population studied and/or a localization that falls within the haplotype structure of the gene.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Human resistin also acts as a pro-inflammatory molecule and stimulates the synthesis and secretion of pro-inflammatory cytokines: TNF-α, IL-6, interleukin-12IL-12 and monocyte chemoattractant protein (MCP)-1 (8) . So, it has been demonstrated that resistin levels in GCF can be considered as a biomarker for studying the severity of periodontitis and/or diabetic patients with periodontitis (12) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated the resistin release is regulated from human neutrophils by Porphyromonas gingivalis lipopolysaccharide (P-LPS) which causes periodontitis (11) . So, resistin levels in gingival crevicular fluid (GCF) can be considered as a biomarker for studying the severity of periodontitis and/or periodontitis in diabetic patients (12) .…”
Section: Introductionmentioning
confidence: 99%